(untitled) (Global Journal of Human-Social Science, 2013)
The relevance of French language in the field of journalism Education in Nigeria is yet to be established This situation cannot be totally divorced from the language policy in Nigeria and the past colonial experience of the country where English was placed at vantage position compared to French language in all spheres of life in Nigeria However researchers and experts in the field of journalism and mass communication education have worked extensively on the significant value of English language and indigenous languages in journalism education Nigeria but there is dearth of research in the area of French language The researcher therefore investigated the relevance of French language to journalism education in Nigeria Simple rando m sampling technique was used to select a higher institution of learning in Ibadan Oyo state A total number of 125 students of mass communication at the Polytechnic Ibadan participated in the study Four research questions were raised and answered The only instrument used for data collection was QMCSAFL The data collected were analyzed using descriptive statistics of PPMC correlation T test and Chisquare The results show that Kn owledge of French language has significant effect on Journalism Education in Nigeria at X Calculated 9 44 50 greater than X Critical 9 16 9 at P 0 000 0 05 There is no relationship between attitude and knowledge at r 0 065 p 0 05